Digitalisasi Layanan Kepolisian: Studi Tentang Efektivitas dan Kendala dalam Penggunaan “Polri Super App” Untuk Pelayanan Publik - Majid, Abdul Majid Zainuddin; Ahmad, Jamaluddin; Nonci, Nurjannah; Astuti, Yayuk (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the implementation of the Polri Super App in the service of issuing Police Record Certificates (SKCK) at the Parepare District Police, by highlighting user responses, officer readiness, and technical and social challenges in the utilization of this digital service. A qualitative approach was employed through in-depth interviews, surveys, and field observations conducted from March to April 2025. The findings show that although the application is considered to improve service efficiency, there are still barriers in the form of low user digital literacy, limited officer training, and technical constraints such as data synchronization and system errors. Additionally, infrastructure gaps in certain areas also hinder equitable access. This research recommends strengthening application features, regular training for officers and users, and inclusive policies that accelerate the transformation of technology-based public services